PrEP in India's HIV Prevention Policy in the Era of Social Media and Sex Positivity - Anindya Kar; Dinesh Bhugra; Shuvankar Mukherjee; Agnibho Mondal; Aaditya Suresh Kumar (University Library System, University of Pittsburgh, 2020)
Introduction: The global revolution of online social media and connectivity had a tremendous effect on sexual behavior in both developed and developing countries. This global change is influencing the societal structure and existing social principles. Moreover, it has a significant impact on the epidemiology of different infectious diseases, especially HIV. Discussion: India is one of the most diverse democratic countries that has undergone a social-cultural transition in the last decade. However, having the second-highest HIV infection rate in the world, India does not have any other new prevention tools in their national HIV prevention strategy. Pre-Exposure Prophylaxis (PrEP), a boon of HIV prevention widely used in different countries, is still not implemented in India. The concept of "Digital India" by the Government of India is giving wide access of internet to the people of India. Furthermore, people are exposed to social media, and that is impacting their sex seeking behavior. Interestingly, recent legal changes in India promotes sex positivity. It also calls for introspection on existing HIV preventive strategies. Conclusion: Given the current scenario of PrEP and other existing preventive measurements of HIV, further research is needed to determine the acceptance and efficacy of PrEP and improve engagement in care for individuals in India. Various international studies recommend effective implication of PrEP to reduce the rate and economic burden of HIV infection.